KONSEP TEORI H, PENGARUH BI RATE, KURS TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) PERIODE TAHUN 2009 – 2017 - Roikhan Mochamad Aziz; Awaludin Syarif Abdulah (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
This study was to examine the general effects BI Rate (Bank Indonesia’s Rate) and Exchange Rate (Rupiah againts USD) as macroeconomic variables againts Jakarta Composite Index atau JSX Composite and the information about possibility of H-Teory that might be used. Descriptive quantitative research method was used to this research. Secondary data technique collection with Eviews version 4.0 as a tools to proceed it. The datas of this research was taken from Central Statistics Agency (BPS), Bank Indonesia (BI, and Indonesia Stock Exchange (IDX) from 2009 – 2017 period. The result showed that BI Rate and Exchange rate has no significant influence on JSX Composite, this was seen from the results the test for the whole varibales in the model was done using the F-test, showed that the F-statistic value of 2212.537 with the probability value of 0.000000 was smaller than α = 0.05 which means H0 was accepted. This means that the BI rate and exchange rate were tested together (simultaneous) did not significantly affect the JSX Composite with a confidence level of 0.984719 or 98.47 percent. H theory here, is expected to be a meeting point in any test that includes the dimensions of Worship.